Geomorphosite Comparative Analysis in Costa Rica and Cameroon Volcanoes - Quesada Román, Adolfo (2020)
Volcanic geoheritage is an emerging field with limited assessments and particular methodological approaches worldwide. The scarcity of volcanic geomorphosite evaluation is higher in tropical countries, particularly developing ones such as Costa Rica and Cameroon. To contribute to reducing this gap in the literature, we evaluate and compare the geomorphosites of the Irazú and Eboga volcanoes, which are renowned massifs for both their natural and their cultural qualities in their respective countries. We used an integrated approach for the inventory and management of volcanic heritage crossing geomorphological and cultural information in order to promote geotourism among all their geodiversity. The study shows that Irazú and Eboga volcanoes are representative for Costa Rica and Cameroon. This information is critical for the promotion of geotourism to a larger public through geoconservation. Our results demonstrate the importance and value that these volcanoes have in promoting and preserving geoheritage in Costa Rica and Cameroon. It is our hope that these outputs may encourage new research in regions less studied tropical volcanic regions. The methodology used proves to be a useful tool in evaluating geomorphological heritage in tropical volcanic environments. Consequently, our study aims to enhance the state of the art of tropical volcanic geoheritage.